Hubert Harrison : the struggle for equality, 1918-1927 - Perry, Jeffrey B., 1946- (Columbia University Press, 2021)
"The St. Croix-born, Harlem-based Hubert Harrison (1883-1927) was a brilliant, class and race conscious writer, orator, editor, educator, book reviewer, political activist, and radical internationalist. Considered the most class conscious of the race radicals and the most race conscious of the class radicals of his era he was described by J.A. Rogers as "perhaps the foremost Aframerican intellect of his time" and by A. Philip Randolph and others as "the father of Harlem radicalism." In this second volume biography covering 1918 to 1927, Jeffrey Perry follows Harrison as he resurrects The Voice, the first newspaper of the "New Negro Movement" (1918); edits The New Negro monthly "intended as an organ of the international consciousness of the darker races-especially of the Negro race" (1919); serves as principal editor of Marcus Garvey's Negro World reshaping and developing that paper into the preeminent radical, race conscious, political and literary publication of that time (1920); publishes When Africa Awakes: The 'Inside Story' of the Stirrings and Strivings of the New Negro in the Western World (1920); and makes clear his pioneering role as the founder and driving force of the "New Negro Movement" (years before Alain Locke's 1925 publication of the New Negro). Working from his race conscious radical internationalist perspective, he is a prolific writer of articles, editorials, theatre and book reviews for a wide range of publications, he lectures widely, and he interacts with, and often openly criticizes, prominent individuals (like Du Bois and Marcus Garvey) and organizations as he struggles for democracy and equality in America."--